Transcriptomes analysis of Pichia kudriavzevii UniMAP 3–1 in response to acetic acid supplementation in glucose and xylose medium at elevated fermentation temperature. (July 2022) - Rahman, Khadijah Hanim Abdul; Najimudin, Nazalan; Ismail, Ku Syahidah Ku
Abstract: The yeast Pichia kudriavzevii is gaining attention as a potential lignocellulosic bioethanol producer due to its multiple stress tolerance characteristics. RNA sequencing was performed to analyze the transcriptomics profiling of an isolated strain, Pichia kudriavzevii UniMAP 3–1 in response to acetic acid supplementation at 40ºC in individual glucose and xylose medium. Acetic acid was found to be consumed simultaneously with glucose when grown in glucose media. Transcriptomics profiling revealed that the response of P. kudriavzevii UniMAP 3–1 towards acetic acid includes activation of differentially expressed genes (DEGs) involved in tricarboxylic acid (TCA) cycle, ATP-binding cassette (ABC) transporters, and folding, sorting and degradation, both in glucose and xylose media. Conversely, DEGs involved in energy metabolism were only apparent in xylose media. DEGs categorized under glycolysis, lipid metabolism, amino acid metabolism and hexose transporters are mainly repressed in response to acetic acid supplementation. These results provide new insights on P. kudriavzevii response to acetic acid supplementation in glucose and xylose media during high temperature fermentation, and serve as an important basis to uncover the regulatory mechanisms involved. This study will also provide reference for future studies in developing engineered strains possessing high tolerance to inhibitors at high temperature bioethanol production. Graphical Abstract: ga1 Highlights: First study on whole transcriptomes of thermotolerant Pichia kudriavzevii. P. kudriavzevii UniMAP 3–1 were able to consume acetic acid during fermentation. Acetic acid affects the transcriptomics of P. kudriavzevii UniMAP 3–1. During acetic acid consumption, TCA cycle genes were activated.